Attribute-based revocable collaborative access control scheme - Changgen PENG; Zongfeng PENG; Hongfa DING; Youliang TIAN; Rongfei LIU (Tongxin xuebao)
To solve the dynamic update of access rights in attribute-based collaborative access control, a novel scheme was proposed with the revocation of attribute, user and collaborative policy.A formal definition and a security model were presented, the group-based attribute group were changed to reflect the update of rights, and further, an efficient re-encryption algorithm was used to realize the immediate revocation of attributes and users.The translation value was used to achieve the revocation of collaborative policy by update corresponding ciphertext.The security analysis shows the scheme can guarantee data confidentiality, forward/backward security, and resist collusion attack under chosen plaintext attack.Compared with the related works, the proposal achieved more complete and efficient revocation scheme.